Distribution of Neisseria meningitidis serogroup b (NmB) vaccine antigens in meningococcal disease causing isolates in the United States during 2009–2014, prior to NmB vaccine licensure. Issue 5 (November 2019) - Chang, How-Yi; Vuong, Jeni; Hu, Fang; Liberator, Paul; Chen, Alex; Kretz, Cecilia B.; Blain, Amy; Hao, Li; Retchless, Adam C.; Whaley, Melissa J.; Anderson, Annaliesa S.; Wang, Xin
Highlights: One or more of the three NmB vaccine antigens (FHbp, NadA, and NhbA) were detected in all U.S. meningococcal isolates tested in this study. The predominant vaccine antigen types among NmB isolates are FHbp peptide 1 (B24/1.1, 34.5%), NadA-1.1 (97.5%) and NhbA p0005 (26.6%). The prevalent FHbp peptides identified in the current study (2009–2014) are similar to those reported previously (2000–2008). Abstract : Objectives: Two Neisseria meningitidis serogroup B (NmB) vaccines are licensed in the United States. To estimate their potential coverage, we examined the vaccine antigen diversity among meningococcal isolates prior to vaccine licensure. Methods: NmB vaccine antigen genes of invasive isolates collected in the U.S. from 2009 to 2014 were characterized by Sanger or whole-genome sequencing. Results: During 2009–2014, the predominant antigen types have remained similar to those reported in 2000–2008 for NmB and 2006–2008 for NmC, NmY, with the emergence of a few new types. FHbp of subfamily B or variant 1 (B/v1) remained prevalent among NmB whereas FHbp of subfamily A or variant 2 and 3 (A/v2-3) were more prevalent among non-NmB. FHbp peptide 1 (B24/1.1) remains the most prevalent type in NmB. Full-length NadA peptide was detected in 26% of isolates, primarily in NmB and NmW. The greatest diversity of NhbA peptides was detected among NmB, with p0005 as the most prevalent type. Conclusions: The prevalence and diversity of the NmB vaccine antigens have remained stable with common antigen types persisting over time. The data collected prior to NmB vaccine licensure provide the baseline to understand the potential impact of NmB vaccines on antigen diversity and strain coverage.